2009
DOI: 10.1177/1866802x0900100106
|View full text |Cite
|
Sign up to set email alerts
|

From Party Systems to Party Organizations: The Adaptation of Latin American Parties to Changing Environments

Abstract: is an Open Access publication. It may be read, copied and distributed free of charge according to the conditions of the Creative Commons Attribution-No Derivative Works 3.0 License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Thus, in addition to the elements inherent in inter-party competition in democratic regimes, it is important to analyze the evolution of the profile of political projects in electoral environments. Authors such as Wills-Otero (2009) report that many parties tend to disappear after poor electoral results in elections where they traditionally performed better. Specifically, many small parties with a strong expression in European parliamentary and or in regional elections tend to disappear from the political map more quickly after scant votes (especially in terms of percentage) in these elections.…”
Section: The Datamentioning
confidence: 99%
“…Thus, in addition to the elements inherent in inter-party competition in democratic regimes, it is important to analyze the evolution of the profile of political projects in electoral environments. Authors such as Wills-Otero (2009) report that many parties tend to disappear after poor electoral results in elections where they traditionally performed better. Specifically, many small parties with a strong expression in European parliamentary and or in regional elections tend to disappear from the political map more quickly after scant votes (especially in terms of percentage) in these elections.…”
Section: The Datamentioning
confidence: 99%
“…Essa nova agenda de estudos surge de dois movimentos que se sobrepõem: as novas democracias e seus partidos políticos e o incremento científico na ciência política que se dedica à área de partidos políticos. A centralidade dos partidos políticos em de-mocracias de terceira onda, essencialmente na América Latina, na África e nos regimes pós-comunistas do Leste Europeu e de alguns países como Índia, Turquia, Israel, Coreia do Sul e Japão, colocou em questão a importância das relações entre partido e eleitor e do funcionamento da democracia (Cox and Rosenbluth, 1994;Yishai, 2001;Diamond, 2003;Bogaards, 2004;Öhman;Square;London, 2006;Wills-Otero, 2009;Kwak;Janda, 2010;Hellmann, 2011;Tavits, 2013). As realidades impostas por essas recentes democracias levaram os teóricos a reexaminarem as teses sobre a prevalência de determinados modelos de partidos políticos -em maior medida dos partidos de massa como pilares das democracias industriais avançadas.…”
Section: Apresentaçãounclassified
“…More specifically, base-level routinization is assumed to have implications for elite routinization, as elites are recruited from or by the same party base (Panebianco 1988;Katz and Mair 1995). Yet various studies have indicated that outsider recruitment can co-exist with a routinized party base (Kitschelt 1994;Levitsky 1998;Wills-Otero 2009), suggesting that traditional party models need to be systematically 'disaggregated'.…”
Section: Conceptualizing Multi-level Routinizationmentioning
confidence: 99%
“…Once doing so it becomes clear that the routinization of the party baseor base-level routinizationdoes not necessarily impose constraints on leadership behavior (Wills-Otero 2009;Scarrow, Webb, and Farrell 2001). This might be the case, for instance, because the party elite renews itself through outsider recruitment for high party positions, putting people in charge who are not socialized into the organization as followers (hence do not form part of the party base) and who therefore might willingly bypass party rules (Levitsky 1998, 82-83;Burgess and Levitsky 2003).…”
Section: Conceptualizing Multi-level Routinizationmentioning
confidence: 99%